Pilot Study of Instrument to Measure Effect of School Climate, Teachers’ Commitment, Teachers’ Motivation and Teachers’ Job Satisfaction Towards Teachers’ Work Performance - Lai Eng Fei, Evonne; Gregory K Han, Crispina (International Journal of Engineering and Technology, 2018)
The main focus of this article is to discuss the findings of the pilot study of the instrument about "The Effect of School Climate, Teachers’ Commitment, Teachers’ Motivation and Teachers’ Job Satisfaction towards Teachers’ Work Performance", which has been adapted by researchers. The pilot study sample was 137 teachers of secondary school involved in the survey. Factor analysis was conducted using the Statistical Package of Social Science (SPSS) version 21 and the reflective measurement model in the Structural Equation Modeling (PLS-SEM) was also conducted in this study. The validity and reliability of External Load (> 0.6), AVE (> 0.5), Composite Reliability and Cronbach’s alpha are (> 0.7); and the Discrimination Validity based on the Fornell-Larcker Criterion (latent value exceeds the latency correlation) was fulfilled. The validity and reliability shown indicate that the instrument is suitable for the actual study.